KONSEP PENDIDIKAN AKHLAK PERSEPEKTIF IMAM AL-GHAZALI DAN AKTUALISASINYA PADA PENDIDIKAN ISLAM DI INDONESIA - Fitriyani Sanuhung; Yazida Ichsan; Nur Rahma Setyaningrum; Alif Fajar Restianti (Journal of Research and Thought on Islamic Education (JRTIE), 2021)
Abstract: The purpose of this study is to find out the concept of moral education proposed by Imam Al Ghazali and its relation to Islamic education in Indonesia and its contextualization of current Islamic education. Moral education is still often a topic that is discussed until now the phenomenon of criminal acts that occur in the community is a serious problem for the decline of people's morals. This research was conducted using the literature method by taking data from books, journals, and other websites. Moral education according to Imam Al Ghazali defines morals as one of the attitudes contained in humans and is the cause of the emergence of other behaviors, as easy that does not require prior planning The concept of Imam Al Ghazali's moral education is still relevant to be used today. Keywords. Character education, Imam Al Ghazali